Costly avoidance of Pavlovian fear stimuli and the temporal dynamics of its decision process - Boschet, Juliane M.; Scherbaum, Stefan; Pittig, Andre (Scientific Reports, 2022)
Conflicts between avoiding feared stimuli versus approaching them for competing rewards are essential for functional behavior and anxious psychopathology. Yet, little is known about the underlying decision process. We examined approach-avoidance decisions and their temporal dynamics when avoiding Pavlovian fear stimuli conflicted with gaining rewards. First, a formerly neutral stimulus (CS+) was repeatedly paired with an aversive stimulus (US) to establish Pavlovian fear. Another stimulus (CS−) was never paired with the US. A control group received neutral tones instead of aversive USs. Next, in each of 324 trials, participants chose between a CS−/low reward and a CS+/high reward option. For the latter, probability of CS+ presentation (Pavlovian fear information) and reward magnitude (reward information) varied. Computer mouse movements were tracked to capture the decision dynamics. Although no more USs occurred, pronounced and persistent costly avoidance of the Pavlovian fear CS+ was found. Time-continuous multiple regression of movement trajectories revealed a stronger and faster impact of Pavlovian fear compared to reward information during decision-making. The impact of fear information, but not reward information, modestly decreased across trials. These findings suggest a persistently stronger weighting of fear compared to reward information during approach-avoidance decisions, which may facilitate the development of pathological avoidance.
CRIS-Team Scopus Importer:2022-05-06